REDESAIN PONDOK PESANTREN PUTRA NURUL RABI DI KECAMATAN KELUMPANG TENGAH - Sari, Widya Puspita; Anhar, Pakhri (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
The redesign of the Putra Nurul Rabi Islamic Boarding School in Kelumpang Tengah District was motivated by inadequate facilities and infrastructure both in terms of physical and psychological needs of students. The purpose of the redesign is to create a forum for religious education in conveying and developing Islamic teachings by maintaining the salaf tradition, providing convenience, comfort, and supporting user activities. The application of the concept of sorogan and bandongan with the method arrangement, application of bright colors, materials and textures, and outdoor space.